Feasibility pilot study of a Japanese teaching kitchen program - Baden, Megu Y.; Kato, Sarasa; Niki, Akiko; Hara, Tomoyuki; Ozawa, Harutoshi; Ishibashi, Chisaki; Hosokawa, Yoshiya; Fujita, Yukari; Fujishima, Yuya; Nishizawa, Hitoshi; Kozawa, Junji; Muraki, Isao; et al. (Frontiers in Public Health, 2023)
Background: This pilot study examined the feasibility of a new lifestyle modification program involving a "Teaching Kitchen" in Japan. Our goal was to explore 1) feasibility of the program; 2) acceptability for class frequency (weekly vs bi-weekly); and 3) changes in biometrics, dietary intakes, and lifestyle factors.Methods: A total of 24 employees with obesity in a Japanese company were recruited.Participants were randomly divided into two groups (weekly or bi-weekly group), each attending the program consisting of four two-hour classes (lectures on nutrition, exercise, mindfulness, and culinary instructions). Participants were observed for changes in dietary intakes, biometrics, and health related quality of life over the subsequent three months. We tested the between-group differences in changes using linear mixed-effect models.Results: The program completion rates were 83.3% in total (91.7% for weekly group and 75.0% for bi-weekly group). From baseline to post-intervention, significant decreases were observed in weight (p<0.001), body mass index (p<0.001), diastolic blood pressure (p=0.03), body fat mass (p<0.001), and dietary intakes in total fat (p=0.03) and sodium (p=0.008) among 17 participants who were available for measurements. Improvements in biometrics remained significant one month after the intervention (all p≤0.03 in 14 participants).Participants' health related quality of life was significantly improved in bodily pain, general health, vitality, and mental component score (all p≤0.047).Conclusions: The new Japanese Teaching Kitchen program is feasible with high program completion rates in Japanese office workers with obesity. While this was a small feasibility study, significant multiple improvements in dietary intakes, biometrics, and health related quality of life suggest that this line of inquiry warrants further exploration to address obesity and obesity-related diseases in Japan.